Further species and range extensions of Amazonian bryozoans: chipping away at the iceberg - Wood, Timothy S.; Okamura, Beth (Zootaxa, 2022)
A bryozoan survey conducted in the Amazon Basin in the vicinities of Manaus and Santarém during the high water season (May, 2018) revealed four new species described here: Fredericella adrianoi n. sp., Plumatella divae n. sp., Plumatella hartikainenae n. sp., and Plumatella spencerjonesae n. sp. Two of these species were encountered only once, suggesting that other undescribed species are likely to occur in the area. Range extensions were determined for two additional species: Plumatella pirassununga and Timwoodiellina natans. In addition, colonies were collected for the first time for two species previously known only by their statoblasts: Plumatella siolii and Plumatella marcusi. Statoblasts of Tapajosella elongata were encountered near Manaus, but the colonies remained elusive. The discovery of new species collected during two expeditions to the Amazon Basin in different seasons and years suggests that further diversity remains undetected in this and other poorly studied regions of the world. With few exceptions, plumatellid colonies described so far from the Amazon Basin are very similar in appearance, with branches wholly attached to the substratum and body walls that are soft, colorless, and transparent.